The effect of reduced glutathione on the toxicity of silver diamine fluoride in rat pulpal cells - KIM, Seunggun (J Appl Oral Sci, 2021)
INTRODUCTION: Due to its ability to arrest untreated dental caries, silver diamine fluoride (SDF) has been advocated for indirect pulp capping procedures. However, the high concentrations of silver and fluoride in SDF raise concerns about its biocompatibility to pulpal tissues. OBJECTIVES: This study aimed to investigate the effect of SDF on the viability, alkaline phosphatase (ALP) activity, and morphology of pulpal-like cells (RPC-C2A) and to evaluate the influence of reduced glutathione (GSH) on SDF-induced cytotoxicity and deposit formation on dentin. METHODOLOGY: The cytotoxicity of diluted 38% SDF solutions (10-4 and 10-5), with or without the addition of 5 mM or 50 mM GSH, was evaluated at 6 and 24 hours. Cell viability was detected using WST-8 and the effect on ALP activity was performed using an ALP assay kit. Cell morphology was observed using a phase-contrast microscope. Scanning electron microscopy analysis was conducted to evaluate the effect of GSH incorporation or conditioning on SDF-induced deposit formation on dentin discs. Cytotoxicity data were analyzed by two-way analysis of variance (ANOVA) and Tukey post hoc tests (p<0.05). RESULTS: There were significant differences between the groups. The results demonstrated that all tested SDF dilutions caused a remarkable cytotoxic effect, while the addition of GSH prevented SDF-induced damage at 6-hour exposure time in the higher dilution of SDF. Dentin treated with plain SDF or GSH-incorporated SDF solution showed deposit formation with occluded dentinal tubules, unlike the other groups. CONCLUSION: SDF severely disturbed the viability, mineralization-ability, and morphology of pulpal-like cells, while controlled concentrations of GSH had a short-term protective effect against SDF-induced damage. GSH showed an inhibitory effect on SDF-induced dentinal deposit formation. Further research is warranted to evaluate the effect of GSH on caries-arresting, anti-hypersensitivity, and antibacterial functions of SDF.